How to protect your new-born from neonatal death: Infant feeding and medical practices in the Gambia. (January 2017) - O'Neill, Sarah; Clarke, Ed; Peeters Grietens, Koen
Abstract: Since the 1990s, the reduction of under-five child-mortality has been a priority for the WHO (Millennium Development Goal 4). In the last two decades, the greatest reduction has occurred in children older than 1 month, while neonatal mortality (the first 28 days of life) has declined more slowly. Neonatal deaths, estimated at approximately 4 million annually, now account for more than 40% of deaths worldwide. Bacterial infections are the leading cause of neonatal deaths. Although risk factors for community and hospital based infections potentially leading to neonatal sepsis are well researched, local people's childcare practices in the neonatal phase are poorly understood by clinicians and biomedical researchers. This paper is based on ethnographic research on neonatal caring practices in rural Gambia. We show that many practices centre on protecting the newborn from sicknesses that are believed to be caused by spirits and other supernatural inflictions. Other caring and nourishing practices are performed to enhance the baby's physical, cognitive and moral development making him/her a full member of the community.